Comparative Phytochemical and Physicochemical Study of Tulsi (Ocimum sanctum) and Haldi (Curcuma longa): Comparative Phytochemical and Physicochemical Study of Tulsi (Ocimum sanctum) and Haldi (Curcuma longa) - Srivastav, Renu (International Journal of Pharmaceutical & Biological Archive, 2018)
Curcuma longa belongs to family and ocimum sanctum belongs to family lamiaceae. The phytochemical and physicochemical analysis was carried out for tulsi and haldi and haldi and a comparative study were done. Determination of total ash, acid insoluble, water soluble ash of tulsi and haldi were carried out by using standard procedure. The phytochemical screening has been done for different extract it revealed the presence of alkaloid, flavanoid, tannin, carbohydrate. Phytochemical and physicochemical parameters of Tulsi and haldi were stablished for their identification. The present study is focused on phytochemical and physicochemical study on haldi and tulsi. The qualitative physicochemical analysis was performed for the detection of secondary metabolites (viz. alkaloid, protein, tannin, saponin etc.).